Transcriptomics: A powerful tool to evaluate the behavior of foodborne pathogens in the food production chain. (November 2019) - Lamas, Alexandre; Regal, Patricia; Vázquez, Beatriz; Miranda, José Manuel; Franco, Carlos Manuel; Cepeda, Alberto
Abstract: In recent years, the development of high-throughput transcriptomic tools such as RNA-seq and microarrays have revolutionized biological scientific research. Despite these techniques being widely used in biomedical research, their introduction into the field of food microbiology is still limited. However, transcriptomic research is of great importance to fully understand the resistance mechanisms and metabolic pathways involved in foodborne pathogen survival from farm to fork. Throughout this review, the main transcriptomic techniques available are described and discussed. Then, the main studies where transcriptomics were used to evaluate survival of foodborne pathogens in the different conditions of the food production chain are evaluated. Particularly, studies focused on biofilm formation, the food matrix and its environment, heat treatments, acid resistance, biocides, and food preservatives were specially reviewed. The data obtained from these studies are of great importance to develop new control strategies in any point of the food production chain. Graphical abstract: Unlabelled Image Highlights: The use of transcriptomics tools in food microbiology is still limited. Transcriptomic changes are caused by common food chain environmental conditions. Transcriptomics technologies reveal resistance mechanisms of food-borne pathogens. Transcriptomic data is useful to develop efficient biocides and food preservatives.